'I am someone, I am not invisible': Exploring the experience of participating in choirs for singers affected by homelessness in Rio de Janeiro. Shelly Coyne. Issue 1 (2018) - Bonshor, Michael; Higgins, Lee; Coyne, Shelly
No abstract available